Electronics for artists adding light, motion, and sound to your artwork - Field, Simon (Chicago Review Press, 2015)
"With today's modern technology--LEDs, servomotors, motion sensors, speakers, and more--artwork can incorporate elements of light, sound, and motion for dramatic effects. Author and educator Simon Quellen Field has developed a primer for creative individuals looking for new ways to express themselves though electronically enhanced art"--
Includes index
Description based on print version record
Keywords: Kunst; Art and electronics; Art -- Technique